ANALYSIS OF PRODUCTION CYCLE ACTIVITIES ON THE ASM-AS CABLE PROJECT USING MANUFACTURING CYCLE EFFICIENCY IN THE WIRE HARNESS INDUSTRY - Sadiq Ardo Wibowo; Taufiq Rahman; Firstnanda Rachellia Pramiesty (Journal of Industrial Engineering Management, 2023)
PT ABC is a company that produces various types of wire harnesses to produce cable assemblies. Wire harnesses are used in a wide variety of electronic products, such as motor vehicles, airplanes, industrial machines and household appliances. In this study the product that will be the object of this research is the wire harness assembly PN 03230462-0101 which is included in the ASM-AS cable project which has a long assembling lead time, this is because this PN is composed of several small PNs, namely PN 03218291- 01, 03218572- 01, 03218569-01, 03222900-01, 03218576-01, 03218574-01, 03223128-01, 03230390-01, 03230391-01. Small PN must be assembled first, so the time required will be longer and the process is quite complicated, there is still no clear work instruction in the cable assembly process, another problem is production efficiency which is still lacking based on company data from each each operator's actual production line that works is greater than the allocation of operators that should be. So that conditions like this cause a decrease in productivity and profits earned by the company. Project cable ASM-AS PN 03230462-0101 is one of the processes that will be improved using a manufacturing cycle efficiency approach. The number of value-added activities is 2,384 seconds, while non-value-added activities are 2,565 seconds, impacting productivity and MCE by 48%. The act of reducing non-value added activities to 987.30 seconds increases MCE to 68% with production flow optimization, automation and stock management